How Bees Make Honey - Ramsay, Helena (Evans Brothers Limited, 1997)
We learn about the short but hectic life of the honey bee. We discover how these hard working insects find and collect nectar and turn it into honey.
Keywords: Juvenile Non Fiction / Animals / Bees / Honey Making